Observasi Pembelajaran SLBA – C di Sekolah SLBA Karya Murni Medan - Sitanggang, Nove; Sirait, Inggrid (Lumbung Pare Cendekia, 2024)
Special Schools (SLB) are educational institutions designed to provide educational services to children with special needs, such as physical, mental and sensory disabilities. SLB has a curriculum that is tailored to the individual needs of students, with the aim of developing their potential optimally. This school provides a supportive environment, both in terms of teaching, facilities and human resources, to help students achieve independence and a better quality of life. The learning approach applied at SLB focuses more on developing life, social and basic academic skills, while still prioritizing the principles of inclusivity and respect for diversity. The results of the community service show that the learning process is more focused on developing life skills, social interactions, and student independence in living everyday life. Teachers are very much needed in accompanying students in the ongoing teaching and learning process.